Ammonium Uptake Rates in a Seagrass Bed under Combined Waves and Currents - Gillis, Lucy G.; Paul, Maike; Bouma, Tjeerd (Frontiers in Marine Science, 2017)
In coastal locations seagrass beds are exposed to various hydrodynamic forces that can include waves and/or unidirectional currents. Differences in these forces may be expected to alter nutrient (such as phosphorus and nitrogen compounds e.g., ammonium) uptake rates by seagrass leaves. We investigated in a laboratory flume how high and low velocities with the absence or presence of waves control ammonium absorption. Our results showed that low currents with waves had the highest nutrient uptake compared to all other treatments. This result was ascribed to a combination of mechanisms. The waves may have influenced turbulence and thereby the water movement around the leaf surface, whilst the low current enabled the canopy to remain upright with an open structure, thereby allowing leaves to be exposed to a greater exchange of ammonium rich water. Although, higher currents with waves might have increased turbulence, bending under the high current squeezed the canopy into a compact closed structure. This study indicates that there are broader implications of the observed mechanisms of nutrient uptake, for instance how they depend on the plant morphology such as the leaf area, length and flexibility.